2020
DOI: 10.21037/tp.2019.09.09
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder: definition, epidemiology, causes, and clinical evaluation

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social communication and the presence of restricted interests and repetitive behaviors (1). In 2013, the Diagnostic and Statistical Manual of Mental Disorders-5 th edition (DSM-5) was published, updating the diagnostic criteria for ASD from the previous 4 th edition (DSM-IV) (Table 1) (1,2).In DSM-5, the concept of a "spectrum" ASD diagnosis was created, combining the DSM-IV's separate pervasive developmental disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
237
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 547 publications
(354 citation statements)
references
References 105 publications
1
237
1
14
Order By: Relevance
“…Therapy robots are generally employed to deliver treatment for people with physical and mental diseases, such as Autism Spectrum Disorder (ASD). A recent review reported statistics showing an annual increase in the number of children with ASD, starting from 1 out of 1000 children in 1970 up to 1 out of 59 children in 2018 [42]. Thus, the need for innovative care and proper attention for ASD children is compelling.…”
Section: The Importance Of Facilitating Human-robot Interactionmentioning
confidence: 99%
“…Therapy robots are generally employed to deliver treatment for people with physical and mental diseases, such as Autism Spectrum Disorder (ASD). A recent review reported statistics showing an annual increase in the number of children with ASD, starting from 1 out of 1000 children in 1970 up to 1 out of 59 children in 2018 [42]. Thus, the need for innovative care and proper attention for ASD children is compelling.…”
Section: The Importance Of Facilitating Human-robot Interactionmentioning
confidence: 99%
“…As one of the most frequent and serious neurodevelopmental conditions, ASD accounts for significant burden in public health, with an estimated annual total cost of $250 billion in the United States [7]. Approximately 1.6% of American children aged 8 years old had an ASD and it is estimated an international prevalence of 0,76% [8,9]. Epidemiology also estimate that more patients are men, with the rate of 3:1 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorders are defined as a combination of neurodevelopmental diseases ( Hodges et al, 2020 ). Symptoms are characterized by lack of development of social and emotional relationships, difficulties in the use of language, apathy, rigidity in movements and repetitive and maniac behaviors.…”
Section: Brain Organoids In Autism Spectrum Disordersmentioning
confidence: 99%